Efectividad de dos protocolos de revascularización en piezas con diagnóstico de necrosis: una revisión bibliográfica - Macas Macas, Alba Narcisa (2025)
Regenerative endodontics has been recognized by the American Association of Endodontics as an innovative approach within the field of dentistry aimed at restoring the vitality of the tissues found within the root canal through the stimulation of stem cells, the most common revascularization technique is the induction of the coagulum by means of over-instrumentation but there are other techniques such as the placement of platelet-rich plasma or fibrin-rich plasma. Objective: To compare the effectiveness of two revascularization protocols in dental pieces with a diagnosis of pulp necrosis, in order to determine which of the protocols presents better clinical results. Materials and methods: An exhaustive search was carried out in electronic databases such as PubMed, LILACS and Scielo using search terms related to the central theme. Results: We proceeded to consult 65 articles of which 13 articles were selected as important after a thorough review and evaluation, ensuring that they met the inclusion criteria previously established to carry out an adequate bibliographic review. Conclusion Through the review of the various authors mentioned, it is evident that endodontic revascularization and regenerative treatments are in constant evolution, generating a debate on their efficacy and applicability in different clinical situations. The importance of factors such as early diagnosis, microbiological control, host immunity and precise protocols during the procedures to achieve successful results is highlighted.